Stan świadomości ekologicznej konsumentów żywności z województwa podkarpackiego - Dziedzic, Sylwia (Level of ecological awareness among food consumers from subcarpathian voivodeship, 2007)
In the work there were presented some research results conducted in the year 2004 in Subcarpathia Voivodeship to define a level of ecological awareness among food consumers. The method used in the research was quota random selection (proportional). The results of the author’s own research, presented in the article, were compared to the present ones in literaturę references, thanks to this they reached a higher grade of educational and scientific value. The high level of ecological awareness among food consumers from Subcarpathian Voivodeship was noticed at 5.2% of respondents.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 158-167